The Shining 2bis - Stephen King Jane Austen (Vintage, 2013)
#1 NEW YORK TIMES BESTSELLER • ONE OF TIME'S 100 BEST MYSTERY AND THRILLER BOOKS OF ALL TIME • In this masterpiece of modern American horror that inspired Stanley Kubrick’s classic film, Jack Torrance takes a job as the caretaker of the remote Overlook Hotel. As the brutal winter sets in, the hotel’s dark secrets begin to unravel. “An undisputed master of suspense and terror.” —The Washington Post Jack Torrance’s new job at the Overlook Hotel is the perfect chance for a fresh start. As the off-season caretaker at the atmospheric old hotel, he’ll have plenty of time to spend reconnecting with his family and working on his writing. But as the harsh winter weather sets in, the idyllic location feels ever more remote . . . and more sinister. And the only one to notice the strange and terrible forces gathering around the Overlook is Danny Torrance, a uniquely gifted five-year-old.
Source Google Books a verifier
Keywords: Stephen King; Vintage; fiction; horror fiction; Recherche bibliographique; shining; york; times; bestseller; time; best; mystery; thriller; books; masterpiece; modern; american; horror; inspired; stanley; kubrick; classic; film; jack; histoire